Surgical Management of Abomasal Rupture Due To Umbilical Hernia in a 4 Month Calf - M. Madeena Begum; M. Balagangatharathilagar; N. Krishnaveni; A.E. Aiswaryaa; E. Kalaiselvan (The Indian Veterinary Journal, 2023)
Umbilical hernia or omphalocele or exomphalos is the protrusion of abdominal content into the hernial sac at region of umbilicus with intact skin. It occurs mainly due to failure of closure of umbilical ring at birth. It is the most common form of congenital hernia reported in calves.